The pattern of microbial flora in Spontaneous bacterial peritonitis in Cirrhotic patients - Sehrish Jehan Asif, Sehrish Jehan Asif (Journal of Rawalpindi Medical College, 2020)
Introduction: Spontaneous bacterial peritonitis (SBP) is the bacterial infection of ascitic fluid in the absence of other apparent causes. It is the most prevalent and serious infection in cirrhosis and leads to significant morbidity and mortality. The frequency of SBP in hospitalized patients with cirrhosis varies from 7 to 23% in the west and it is around 33% in Pakistan. Our study aim was to determine the frequency of microbial organisms isolated from spontaneous bacterial peritonitis in cirrhotic patients. Material and Methods: We did a cross-sectional study at the Department of Medicine, Fauji Foundation Hospital Rawalpindi for 6 months. Cirrhosis was diagnosed on the bases of clinical, biochemical and ultrasonography findings. Peripheral blood samples were obtained for the evaluation of complete blood cell count, polymorphonuclear leukocyte count, albumin and coagulation parameters. At the same time, the patients underwent paracentesis and a 20ml ascitic fluid sample was taken for culture sensitivity along with routine biochemical examination from the pathology department lab at our hospital. Results: A total of 150 patients were enrolled according to the inclusion criteria of the study. The mean age (yrs) of patients was 32.3+9.31. The frequency and percentages of male and female patients were 70 (46.7) and 80 (53.3) respectively. Frequency and percentages of E Coli and streptococcal pneumonia were 94 (62.7) and 34 (22.7) respectively, whereas frequency and percentages of staph aureus and Klebsiella were 22 (14.7). Conclusion: SBP is quite common in patients with cirrhosis. It should be suspected in all such cases presenting with typical or atypical features. E Coli was the most common causative organisms in our study but gram-positive organisms were quite frequent as well.